Reconceptualizing Cultural Character Education: Integrating Futuristic Pedagogy for Generation Alpha's Local Cultural Preservation - Yunita Yasmin Istiqomah; Yusuf Tri Herlambang; Yeni Yuniarti (Journal of Innovation and Research in Primary Education, 2026)
Generation Alpha, born entirely within the digital ecosystem, faces unprecedented challenges in maintaining connection to local cultural heritage while navigating technology-saturated learning environments. This study explores how futuristic pedagogy can effectively cultivate love for local culture among Generation Alpha students in elementary education. A systematic literature review analyzed 47 peer-reviewed publications from 2020-2025, employing purposive sampling and Miles and Huberman's analytical framework comprising data collection, presentation, reduction, and conclusion drawing. Three critical findings emerged: futuristic pedagogy encompasses six interconnected elements balancing technological competencies with character development; Generation Alpha exhibits seven distinctive characteristics including productive global-local cultural tension; and technology-enhanced strategies, particularly augmented reality applications, effectively bridge digital engagement with cultural authenticity. Analysis revealed that successful cultural character education requires intentional integration of immersive technologies, gamified learning, digital storytelling, and collaborative projects that position students as cultural co-creators.  The findings reconceptualize cultural character education as digitally mediated process requiring strategic integration of technological, cultural, and developmental dimensions. While technology contributes to cultural displacement, appropriately designed digital learning experiences can serve as powerful tools for cultural preservation. Future research should conduct longitudinal studies establishing causal relationships and investigate adaptations for diverse Indonesian contexts.